Dimensions of Yahwism in the Persian period: studies in the religion and society of the Judaean community at Elephantine - Granerød, Gard (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2016)
"The book argues that the Aramaic documents from Elephantine dating to the Achaemenid period offer not only important glimpses of Judaean religion in the Persian period but that the religion of the Judaeans in Elephantine is among the best historically verifiable cases of Persian period Yahwism. The documents have the potential of functioning as an archive that can revise the canonised image of the Judaean religion in the Persian period"--